Phylogenomic Analysis of the Plastid Genome of the Peruvian Purple Maize Zea mays subsp. mays cv. ‘INIA 601’ - Montenegro Cabrera, Juan Daniel (2022)
Peru is an important center of diversity for maize; its different cultivars have been adapted to distinct altitudes and water availability and possess an array of kernel colors (red, blue, and purple), which are highly appreciated by local populations. Specifically, Peruvian purple maize is a collection of native landraces selected and maintained by indigenous cultures due to its intense purple color in the seed, bract, and cob. This color is produced by anthocyanin pigments, which have gained interest due to their potential use in the food, agriculture, and pharmaceutical industry. It is generally accepted that the Peruvian purple maize originated from a single ancestral landrace ‘Kculli’, but it is not well understood. To study the origin of the Peruvian purple maize, we assembled the plastid genomes of the new cultivar ‘INIA 601’ with a high concentration of anthocyanins, comparing them with 27 cultivars/landraces of South America, 9 Z. mays subsp. parviglumis, and 5 partial genomes of Z. mays subsp. mexicana. Using these genomes, plus four other maize genomes and two outgroups from the NCBI database, we reconstructed the phylogenetic relationship of Z. mays. Our results suggest a polyphyletic origin of purple maize in South America and agree with a complex scenario of domestication with recurrent gene flow from wild relatives. Additionally, we identify 18 plastid positions that can be used as high-confidence genetic markers for further studies. Altogether, these plastid genomes constitute a valuable resource to study the evolution and domestication of Z. mays in South America.